Peripheral and Central Factors in Tinnitus - Paul, Brandon (My University, 2016)
Tinnitus is the phantom perception of a sound heard in the absence of a physical sound source. One framework that attempts to explain tinnitus is called the deafferentation model, which asserts that hearing damage precipitates compensatory neural plasticity in the central auditory system, leading to hyperactivity perceived as tinnitus. While considerable evidence supports this view, the role of deafferentation and its effects on central auditory processing are not fully understood. This thesis addresses two questions raised within the model. First, audiometric hearing loss is not always present in tinnitus subjects, so is there evidence of deafferentation in these individuals? The second question concerns the effect of tinnitus with audiometric hearing loss on central auditory processing. Specifically, is auditory attention affected in tinnitus, and if so, how? Following a background review in Chapter 1, Chapter 2 describes a study addressing the first issue, which found evidence for previously undetected hearing loss in tinnitus subjects that distinguishes them from individuals with normal hearing. Chapter 3 addresses the second question, describing an investigation that found that top-down attention appears to operate normally in tinnitus, but the tinnitus-affected region of auditory cortex is insensitive to the influence of attention because it is busy encoding the tinnitus. Chapter 4 describes a background study using non-tinnitus individuals to test this latter conclusion, finding evidence that auditory cortical neurons reacting to stimulus change are concurrently sensitive to top-down attention. This procedure can be used to assess if tinnitus-affected auditory cortical neurons are generally insensitive to input. Chapter 5 discusses the implications of the above empirical findings for understanding the role of deafferentation in tinnitus and tinnitus-related changes that occur in central auditory processing.